KETAHANAN PANGAN DAN KONSUMSI GIZI KELUARGA PETANI PADI PENERIMA DANA BANTUAN LANGSUNG MASYARAKAT BERGULIR (BLMB) - Indriani, Yaktiworo (Lampung University)
This research aims to observe the conduction of BLMB (Bantuan Langsung Masyarakat BergulirÂ â A Direct Aid for the Community) in Intensification of Rice Quality Improvement Program (PMI Padi) and to evaluate the food security and nutritional consumption of the farmer families receiving BLMB.Â This research was conducted by a qualitative approach, based on the community participatory. Research samples are 30 families of three rice farmer groups receiving BLMB in East Lampung Regency. The data were collected from September 2005 to February 2006.Â The result shows that the BLMB in PMI Padi has been well conducted by following the existing direction procedures from the Lampung Province.Â However, some ways of these procedures are different from the existing direction procedures of the Ministry of Agriculture.Â In average, families of the rice farmer have good food security, both in staple food and in total food.Â In addition, their average variety nutritional sufficiency values (NRKG) are also good, but one of the farmer groups has low percentage of energy requirement. Moreover, all groups have low percentages of calcium and iron requirements.Â Only one farmer group has good food security.Â All of its family members in good food security category. The conduction of BLMB has not fully met the food security and nutritional consumption standard of the rice farmers family receiving that program.